Evaluation of the thrombus of abdominal aortic aneurysms using contrast enhanced ultrasound - preliminary results - Łukasiewicz, Adam (Sci Rep, 2016)
It is hypothesized that the degree of vascularization of the thrombus may have a significant impact on the rupture of aortic aneurysms. The presence of neovascularization of the vessel wall and mural thrombus has been confirmed only in histopathological studies. However, no non-invasive imaging technique of qualitative assessment of thrombus and neovascularization has been implemented so far. Contrast-enhanced ultrasound (CEUS) has been proposed as a feasible and minimally invasive technique for in vivo visualization of neovascularization in the evaluation of tumors and atherosclerotic plaques. The aim of this study was the evaluation of mural thrombus and AAAs wall with CEUS. CEUS was performed in a group of seventeen patients with AAAs. The mural thrombus enhancement was recognized in 12 cases, yet no significant correlation between the degree of contrast enhancement and AAAs diameter, thrombus width, and thrombus echogenicity was found. We observed a rise in AAAs thrombus heterogeneity with the increase in the aneurysm diameter (r = 0.62, p = 0.017). In conclusion CEUS can visualize small channels within AAAs thrombus, which could be a result of an ongoing angiogenesis. There is a need for further research to find out whether the degree of vascularization of the thrombus may have a significant impact on the rupture of aneurysms.